A review on applications of nanofluid in evacuated tube heat pipe integrated with compound parabolic concentrator. (2021) - Vijayakumar, P.; Kumaresan, G.; Gokul Kumar, S.; Eswaran, M.
Abstract: The Enhancement of thermal conductivity made researches in nanofluids progress rapidly, though it was started only about a decade ago. Harvesting solar energy is becoming an interest in the people because of its availability and clean, green nature. Compound Parabolic Concentrator is a solar thermal collector, used to concentrate the radiation on a single line of focus, where the tube is placed to receive it. The shortage of conventional fuels and environmental considerations is forcing us to switch towards alternative energy sources like solar energy. Improving the efficiency and performances of solar thermal collectors like CPC may increase the interest of people towards solar energy. The efficiency and performance of a CPC with an evacuated tube can be further increased by utilizing nanofluid, which is used to trap more heat. The heat trapped is efficiently conducted by using a heat pipe, which is a heat transferring device. The nanofluid, filled in heat pipe undergoes phase transition. This review shows that the performance of a CPC with an evacuated tube integrated with heat pipe is increased using nanofluid and there is a wide range of opportunities to increase the utilization of CPC with nanofluids in various fields in the future.